Overexpression of HexCer and LacCer containing 2-hydroxylated fatty acids in cholangiocarcinoma and the association of the increase of LacCer (d18:1-h23:0) with shorter survival of the patients - Silsirivanit, Atit; Phoomak, Chatchai; Teeravirote, Karuntarat; Wattanavises, Sasiprapa; Seubwai, Wunchana; Saengboonmee, Charupong; Zhan, Zhaoqi; Inokuchi, Jin-ichi; Suzuki, Akemi; Wongkham, Sopit (Glycoconjugate journal, 2019)
Alteration of glycosphingolipid (GSL) synthesis is observed in many types of cancer. In this study, we have analyzed the expression of sphingolipids and GSLs in cholangiocarcinoma (CCA) tissues and adjacent normal liver tissues. Neutral lipids were extracted from tissue samples using mild-alkaline treatment method followed by TLC and LC-MS analysis. The expression of ceramides, hexosylceramides (HexCer), and lactosylceramides (LacCer) was altered in CCA tissues, 61.1% (11/18) of them showing an increase whereas 38.9% (7/18) showing a decrease, compared with the adjacent normal tissue. Cers and GSLs containing 2-hydroxylated fatty acids except one LacCer molecular species were overexpressed in CCA tissues, and the increase of LacCer (d18:1-h23:0) was correlated with shorter survival of CCA patients, suggesting the involvement of GSL synthesis and fatty acid hydroxylation in progression of CCA. Taken together, we have demonstrated in this study the increase of GSL synthesis and fatty hydroxylation in CCA, which probably be used as a target for CCA treatment.